Distribution of Polycyclic Aromatic Hydrocarbons in Coal Gangue with Different Metamorphic Degrees. Issue 2 (May 2020) - Chen, Dong; Wen, Xueqin; Zeng, Fangui; Huang, Dongmei
Abstract: The contents of 16 US Environmental Protection Agency (EPA) polycyclic aromatic hydrocarbons (PAHs) in coal gangue samples with different metamorphic degrees (R0, max=1.21%, 1.47%, 1.84%, 2.05%, 3.30%) have been measured by high performance liquid chromatography (HPLC), and the characteristic distributions of PAHs in samples are studied. The results suggest that all the contents of high molecular weight polycyclic aromatic hydrocarbons (HPAHs, 4-6ring), low molecular weight polycyclic aromatic hydrocarbons (LPAHs, 2-3ring), total polycyclic aromatic hydrocarbons and the toxicity of PAHs in samples increase first and then decrease as the increase of vitrinite reflectance. The proportion of LPAHs in the ∑16PAHs decreases first and then increases, while HPAHs is opposite. Furthermore, Ant/(Ant+Phe) ranges from 0 to 0.03, Flua/(Flua+Pyr) ranges from 0 to 0.37, BaA/(BaA+Chr) ranges from 0.04 to 0.14, and total index range from 0.64 to 1.66 in samples, all of which could provide a reference for judging the source of PAHs.